Characterization of Periodontal Structures of Enamelin‐Null Mice. Issue 1 (1st January 2014) - Chan, Hsun‐Liang; Giannobile, William V.; Eber, Robert M.; Simmer, James P.; Hu, Jan C.
Abstract : Background: Enamelin ‐null ( ENAM −/− ) mice have no enamel. When characterizing ENAM −/− mice, alveolar bone height reduction was observed, and it was hypothesized that enamel defects combined with diet are associated with the periodontal changes of ENAM −/− mice. The aim of the present study is to compare the dimension of interradicular bone of ENAM −/− (knock‐out [KO]) with wild‐type (WT) mice, maintained on hard (HC) or soft (SC) chow. Methods: A total of 100 animals divided into four groups were studied at 3, 8, and 24 weeks of age: 1) KO/HC; 2) KO/SC; 3) WT/HC; and 4) WT/SC. Microcomputed tomography was performed, and the following measurements were made between mandibular first (M1) and second (M2) molars: relative alveolar bone height (RBH), crestal bone width (CBW), bone volume (BV), bone mineral content (BMC), and bone mineral density (BMD). The position of M1 and M2 in relation to the inferior border of the mandible was also determined at 24 weeks. All variables were analyzed by one‐way analysis of variance and Dunnett test for pairwise comparisons. Morphologic analyses were conducted on hematoxylin and eosin–stained sections. Results: Radiographically, the enamel layer was absent in ENAM −/− mice. Interproximal open contacts were observed exclusively in ENAM −/− mice, and the prevalence decreased over time, suggesting that a shifting of tooth position had occurred. Additionally, in the two ENAM −/− groups, RBH was significantly lower at 8 and 24 weeks ( P <0.02); CBW, BV, and BMC were significantly less ( P <0.05) at 24 weeks. No differences in BMD were found among the four groups. The molars migrated to a more coronal position in ENAM −/− mice and mice on HC. Histologic findings were consistent with radiographic observations. After eruption, the junctional epithelium was less organized in ENAM −/− mice. Conclusion: The interdental bone density was not affected in the absence of enamelin, but its volume was, which is likely a consequence of alternations in tooth position.